Experimental and Numerical Study the Influence of Sheet Metal Thickness on a Deep Forming Operation of Multi Stages for Hexagonal Cup - Gharrawi, Sabih Salman Dawood AL-; Tuaimah, Ali (Al-Nahrain Journal for Engineering Sciences, 2017)
In this research, experimental and analytical deep drawing of the several-stages design mold is produce hexagonal cup and also proved the influence of the thickness of the sheet on the allocation of strain and laminating in curvature of the cup area for all stages of the drawing. Three stages deep drawing mold was designed and constructed to carry out the experimental work required to produce a hexagonal cup of (28.25 mm by 24.5 mm) , (60 mm) high drawn from a circular flat sheet (80 mm diameter), made from low carbon steel (1006–AISI). Analysis program (ANSYS11.0) to perform the finite element method to accomplish the analytical side of the search. Three types of thickness sheet (tt°= 0.5, 0.7,1 mm) with constant radius of curvature of punch equal to (RRpp =4) mm, radius of curvature of die equal to (RRdd=8 mm)and radius of curvature of wall of die (RRcc= 4 mm) were used. From the experimental and analytical results of the three stages of drawing, it has been found that drawing load less than the more advanced stages of drawing operation on the wall of cup, maximum laminating take place at curvature of the cup area with sheet thickness equal to (tt°=0.5 mm) and maximum thickeningtake place at the at throat cup with sheet thickness equal to (tt°=1 mm), the maximum values of strains (radial, hoop, thickness andeffective)take place at throat cup with sheet thickness equal to (tt°=1 mm).